Fuzzy MCDM Approaches in Sustainability Research: A Literature Review - Oztaysi, Basar; Onar, Sezi Cevik; Cebi, Selcuk; Kahraman, Cengiz (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
Sustainability has emerged as an important concept for solving environmental, economic, and social challenges all over the world. Systems and applications are adopted and revisited as sustainability gain importance. During the adaptation, efficient decision making has been an important tool. Multicriteria Decision Making (MCDM) methods have also gained widespread attention for their ability to support complex decision-making and have been used for sustainability studies. On the other hand, The integration of Fuzzy Set Theory into MCDM has further strengthened existing methods by enabling the modeling of uncertainty and imprecision in expert judgments. This study presents a comprehensive literature review on the application of fuzzy MCDM techniques in sustainabilityrelated research. Using a structured search methodology on the Scopus database, we analyze trends, commonly used techniques, fuzzy set extensions in the field. Furthermore, a content analysis is applied to categorize studies into six thematic areas: Governance and Policy Making, Corporate Sustainability and Planning, Infrastructure and Smart Cities, Waste Management, Supply Chain Management, and Energy Management. The results show that a significant increase in the number of fuzzy MCDM studies on sustainability in recent decade, with TOPSIS, AHP, and VIKOR emerging as the most frequently used methods. Intuitionistic and Pythagorean fuzzy sets are among the most adopted fuzzy extensions.
Keywords: Sustainability; Fuzzy Sets; MCDM; SELECTION; Computer Science